1993
DOI: 10.1021/bi00091a001
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding of nucleosome cores dramatically changes the distribution of ultraviolet photoproducts in DNA

Abstract: Nucleosome core particles undergo a conformational change at ionic strengths below 0.2 mM; the fluorescence anisotropy decay of bound ethidium indicates that under these conditions the particle adopts a highly extended structure. We have measured the distribution of UV-induced DNA damage (primarily cyclobutane-pyrimidine dimers) through a process termed photofootprinting. As the core particle is exposed to ionic strengths below 0.2 mM, the photofootprint pattern changes from that observed for native cores, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Indeed, there has long been evidence for a thermodynamically stable extended form of the nucleosome existing below Ϸ1 mM salt (38,39). Furthermore, UV photofootprinting studies indicate that the DNA in that structure is ''no longer bent to a significant degree,'' although it is still attached to histones (40). We suggest that the fluctuations we observe may represent temporary excursions into a similar open state that also can occur at higher salt concentrations.…”
Section: Dynamic Equilibrium Between Open and Closed States Of A Nucleo-mentioning
confidence: 62%
“…Indeed, there has long been evidence for a thermodynamically stable extended form of the nucleosome existing below Ϸ1 mM salt (38,39). Furthermore, UV photofootprinting studies indicate that the DNA in that structure is ''no longer bent to a significant degree,'' although it is still attached to histones (40). We suggest that the fluctuations we observe may represent temporary excursions into a similar open state that also can occur at higher salt concentrations.…”
Section: Dynamic Equilibrium Between Open and Closed States Of A Nucleo-mentioning
confidence: 62%
“…The same modulation of CPD formation was observed in UV-irradiated isolated nucleosome cores (Gale et al, 1987) which is consistent with a preferential formation of CPDs at sites where the DNA minor groove faces the solution. A similar periodic CPD pattern generated in a DNA loop (Pehrson & Cohen, 1992) and a loss of the periodicity observed in unfolded nucleosomes (Brown et al, 1993) showed that DNA curvature is a major parameter for the modulation of CPD formation in nucleosomes. When polynucleosomes were reconstituted on irradiated calf thymus DNA, and nucleosome cores were isolated, the CPD distribution was similar to that of irradiated nucleosomes, demonstrating that CPDs were preferentially accommodated during nucleosome assembly on mixed-sequence DNA .…”
mentioning
confidence: 61%
“…We note that an intense DNase I cut site, but not hydroxyl radical cut site, also occurs at Ϫ31, being strong in both naked 5 S rDNA and the 5 S nucleosome (star in Fig. 2B, lanes [5][6][7][8]. This reflects the strong sequence specificity of DNase I (28).…”
Section: Characterization Of Reconstituted 5 S Rdnamentioning
confidence: 81%